1987
DOI: 10.4992/psycholres1954.29.1
|View full text |Cite
|
Sign up to set email alerts
|

Intersensory influences on the perception of apparent movement

Abstract: Previous findings on intermodal apparent movement indicate that intersensory effect in it is asymmetric with respect to acoustic and visual systems. It has also been suggested that the difference between the latencies for the light stimulus and for the sound stimulus may coincide with the point of maximum facilitation in perception. The present study examined whether stimulation of the visual and auditory modalities acted symmetrically or reciprocally in their influence on each other under the different stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…On the other hand, directionally conflicting auditory motion had no effect on the perceived direction of visual apparent motion, thus replicating Meyer and Wuerger's (2001) findings, but here using a very different methodology. This asymmetry coincides with the results of the majority of previous research investigating multisensory influences in apparent motion perception (Allen & Kolers, 1981;Anstis, 1973;Ohmura, 1987) as well as in other intersensory biases involving the perception of spatial stimulus attributes (e.g., Welch, 1999). Note that, in their study, Meyer and Wuerger observed that directionally conflicting auditory motion caused a decrement in the accuracy of visual motion direction discrimination.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…On the other hand, directionally conflicting auditory motion had no effect on the perceived direction of visual apparent motion, thus replicating Meyer and Wuerger's (2001) findings, but here using a very different methodology. This asymmetry coincides with the results of the majority of previous research investigating multisensory influences in apparent motion perception (Allen & Kolers, 1981;Anstis, 1973;Ohmura, 1987) as well as in other intersensory biases involving the perception of spatial stimulus attributes (e.g., Welch, 1999). Note that, in their study, Meyer and Wuerger observed that directionally conflicting auditory motion caused a decrement in the accuracy of visual motion direction discrimination.…”
Section: Resultssupporting
confidence: 90%
“…Critically, in their experiments, concurrent visual apparent motion did not influence the perception of auditory motion any more than did a single light flash. Allen and Kolers therefore concluded that it was the temporal arrangement, and not the spatiotemporal arrangement, that was crucial to cross-modal interactions in apparent motion (see also Ohmura, 1987;Staal & Donderi, 1983, for similar results).…”
Section: Multisensory Integration In Motion Perceptionmentioning
confidence: 87%
See 1 more Smart Citation
“…Since the neural processing of visual information is delayed compared to that of auditory information (eg King and Palmer 1985), sound and light will not be perceived as being simultaneous. However, a follow-up study of Ohmura (1987), which took account of the different perceptual latencies by presenting the sound shortly after the first light, confirmed this result. Thus, it seems that the facilitation effect occurs only with sounds being midway between the lights, ie when the sound could act as a link between the visual stimuli.…”
Section: Discussionmentioning
confidence: 82%
“…If the auditory stimuli are asynchronous, however, less visual AM is reported (Gilbert 1939). Others reported that visual AM was not facilitated by concurrent auditory AM but visual AM did facilitate auditory AM (Allen and Kolers 1981;Mateeff et al 1985;Ohmura 1987). Zapparoli and Reatto (1969) found that the direction of visual motion determined whether auditory AM was facilitated and interfered with.…”
Section: Integration Of Bimodal Audiovisual Ammentioning
confidence: 98%